The authority of indeterminate law - Du Plessis, Quentin (Department of Private Law, 2022)
In this dissertation I identify various sources of legal indeterminacy and scrutinize the functions that indeterminacy can play in law. In particular, I focus on the authority of indeterminate law: how it can be that laws of which it is not clear which obligations they impose, nonetheless impose obligations. I argue that there are more sources of legal indeterminacy than is commonly assumed in the literature, and that the role that context plays in the occurrence, functionality and authority of indeterminate legal norms has been largely overlooked. I argue further that indeterminate legal norms can be authoritatively binding just so long as we accept that the nature of the obligation imposed by the norm changes according to whether the legal norm generates a hard case as applied to a particular context.